Biblioshiny-R Application to Map Islamic Audit Research - Maulida, Syahdatul; Kassim, Siti Fatimah Mohd (SMART Insight, 2023)
This research uses a qualitative bibliometric analysis approach using Biblioshiny R software, with the aim of evaluating and investigating the development of literature related to Islamic auditing. This research data was obtained from scientific publications contained in the Scopus database during the period 1997-2023. The research results show that the main journal most active in publishing articles on Islamic auditing is Journal of Islamic Accounting and Business Research, reflecting the focus and contribution of the journal in developing literature on this topic. In particular, the most productive author in this context is Hussainey K, who has made a significant contribution in publishing articles on Islamic audits indexed in Scopus. Keyword analysis shows that “Islamic Banks” emerged as the most frequently appearing keyword related to sharia audit, highlighting the importance of sharia audit in the context of Islamic banking and financial institutions. This research also finds 5 (five) clusters of Islamic audit studies.